Rural Participation in the Territorial Development Processes - Bartol de Imbach, Patricia María (Revista Electrónica Educare, 2012)
This paper discusses the urgency of creating a bridge between social participation and civic capacity building. The permanent dialogue between expert and local knowledge should sustain significant, relevant learning processes from/to the rural areas of the Central American region. Consistency and persistence of these processes will enhance human welfare based on the changes experienced in the rural areas. Numerous Central American initiatives require effective social and institutional participation to be implemented. Education, in its different forms and through its different resources, has the crucial responsibility of helping citizens to take advantage of those initiatives.